(untitled) (Universal International Scientific Journal, 2026)
This article analyzes information attacks affecting the minds of young people in the modern information space, their social and psychological consequences. The concept of spiritual and moral immunity and its role in protecting the minds of young people are studied. Ways to develop a child’s value system, emotional stability and independent thinking through family psychology are shown. It also examines how gender stereotypes affect the social consciousness of young people and the importance of the family in protecting them from information attacks. The article scientifically substantiates the relevance of the family upbringing environment by showing the mechanisms for protecting young people from information threats from a social, pedagogical and psychological perspective.